2008
DOI: 10.1007/s11743-008-1092-4
|View full text |Cite
|
Sign up to set email alerts
|

The HLD‐NAC Model for Mixtures of Ionic and Nonionic Surfactants

Abstract: The HLD-NAC model has been used as an ''equation of state'' to predict the properties of microemulsion (lE) systems formulated with either anionic or nonionic surfactants. The model uses the concept of the hydrophilic-lipophilic difference (HLD) to calculate the chemical potential difference of transferring a surfactant from the oil to the aqueous phase; as a function of formulation variables such as type of surfactant, oil, temperature, electrolyte concentration. The value of HLD is used as a scaling paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 31 publications
5
81
1
1
Order By: Relevance
“…Consistent with this trend is the slightly higher aqueous phase concentration of CK-2,13-E 5.6,ave ( Table 2). In agreement, a recent thermodynamic study concluded for the nonylphenyl ethoxylate/sodium dihexyl sulfosuccinate binary system that the latter increases hydration of the ethoxylate groups, which would increase their polarity, hence promoting their partition to the aqueous phase [37]. In contrast, the contribution of CK-2,13s hydrophobic moiety toward partitioning was not strongly affected by C8bG1 or AOT, evidenced by log K 0,HLB values for the binary surfactant systems and CK-2,13-E 5.6,ave single-surfactant system being similar (Table 5).…”
Section: Surfactant Systemsupporting
confidence: 85%
“…Consistent with this trend is the slightly higher aqueous phase concentration of CK-2,13-E 5.6,ave ( Table 2). In agreement, a recent thermodynamic study concluded for the nonylphenyl ethoxylate/sodium dihexyl sulfosuccinate binary system that the latter increases hydration of the ethoxylate groups, which would increase their polarity, hence promoting their partition to the aqueous phase [37]. In contrast, the contribution of CK-2,13s hydrophobic moiety toward partitioning was not strongly affected by C8bG1 or AOT, evidenced by log K 0,HLB values for the binary surfactant systems and CK-2,13-E 5.6,ave single-surfactant system being similar (Table 5).…”
Section: Surfactant Systemsupporting
confidence: 85%
“…1. A change in the nature of the oil phase would be expected to change the HLD number of the surfactant, i.e., its relative affinity for the oil and water phases [13,31]. In turn, a change in the surfactant HLD number would be expected to alter various physicochemical properties that impact nanoemulsion formation: the distribution of surfactant molecules between the aqueous and organic phases; the spontaneous formation of fine oil droplets at the aqueous-organic phase boundary; the coalescence stability of the droplets.…”
Section: Influence Of Oil Type On Particle Sizementioning
confidence: 99%
“…In turn, a change in the surfactant HLD number would be expected to alter various physicochemical properties that impact nanoemulsion formation: the distribution of surfactant molecules between the aqueous and organic phases; the spontaneous formation of fine oil droplets at the aqueous-organic phase boundary; the coalescence stability of the droplets. For example, as the HLD number moves towards zero, there is usually a decrease in oil-water interfacial tension in a SOW system, which facilitates the spontaneous formation of fine oil droplets [29,31,32]. On the other hand, as the HLD number tends towards zero, the rate of droplet coalescence in SOW systems usually increases, which would cause any fine droplets formed to rapidly grow in size [10,30].…”
Section: Influence Of Oil Type On Particle Sizementioning
confidence: 99%
“…In other words, naphthenic acids are more hydrophilic than oleic acid. Another interesting point of comparison is that sodium oleate, the salt of oleic acid, has a C C of À1.7 [45]. In this case, the neutralization of the fatty acid produced a decrease in C C of 1.7.…”
Section: Analysis Of the Hydrophilic-lipophilic Nature Of Naphthenic mentioning
confidence: 99%